SWOT ANALYSIS ON THE MARKETING STRATEGY DETERMINATION OF FINANCIAL FUND PRODUCT AT BRANCH OFFICE PT PANIN BANK SYARIAH, TBK. MALANG - Fani Firmansyah; Kotijah Fadilah Abdilah (Jurnal Akuntansi Aktual, 2015)
to data from PT Islamic Bank Panin Tbk. Branch Malang for 2011, financial fundsthat have been channeled was 31.354 billion, 19.8 billion for the year 2012, and 4.760 billion for 2013. The above data is data new financing (liquid) in that year. From those data, we can see that from year to year financing funds decreased, therefore in intense competition conditions, PT Panin Bank Syariah Tbk. (PBS) need to define appropriate strategies to obtain a positive response from the community. And also, the products and services offered in accordance with the needs of the people, so that the funds disbursed for financing fund products can be increased and financing products can compete eith both other Islamic Bank and Conventional Bank in Malang. This study will be conducted at branch office ofPT. Islamic Bank Panin Tbk. Malang located at Jl Mgr Sugiopranoto No. 7 Malang, East Java Province. The research is a qualitative study with a descriptive approach. According Moleong (2005) qualitative research as a research procedure that produces descriptive data in the form of words written or spoken of people and behaviors that can be observed. From the results of the SWOT matrix, severalappropriate strategies could be taken by the circumstances Branch Office PT Panin Syariah Bank Tbk. Malang. Based on several things: Segmentation, Targeting, Positioning, Marketing Mix. Based on the research that has been conducted by researchers, there are several conclusions that can be drawn from the results of this study are: a) marketing strategy, especially marketing financial products that are applied by PT Islamic Bank Panin Tbk. Branch Office Malang includes several strategies, namely strategies pick up the ball, referrals, build networks, provide servise excellent, and provide facilities satisfactory to increase confidence and customer satisfaction, so that existing customers will not run away from the bank, b) The results of a SWOT analysis states that PT Islamic Bank Panin Tbk. Malangbranch office has been able to compete in a competitive market competition in Malang.Keywords: SWOT, marketing mix, segmentasi, targeting, positioning